2005
DOI: 10.1124/jpet.105.084913
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Corticotropin-Releasing Factor 1 Receptor Blockade Inhibits Cocaine-Induced Dopamine Release: Correlation with Dopamine Neuron Activity

Abstract: Corticotropin-releasing factor (CRF) is a neuropeptide associated with the integration of the physiological and behavioral responses to stress. Recently, CRF 1 receptor antagonists have been shown to decrease cocaine self-administration and inhibit stress-induced reinstatement of cocaine-seeking behavior. The exact mechanisms underlying this effect are not clear. Based on the large amount of literature demonstrating an association between dopaminergic neurotransmission and reward-related behavior, the aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 32 publications
6
42
0
Order By: Relevance
“…Because of activation of DA autoreceptors and long-loop feedback pathways from forebrain structures, these drugs also inhibit DA cell firing (Einhorn et al, 1988;Lodge and Grace, 2005) via activation of D1 and D2 receptors (Shi et al, 2000). In the present study, we show a decrease in the percentage of spikes in bursts of DA neurons after acute amphetamine (A+1), consistent with previous work (Lodge and Grace, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Because of activation of DA autoreceptors and long-loop feedback pathways from forebrain structures, these drugs also inhibit DA cell firing (Einhorn et al, 1988;Lodge and Grace, 2005) via activation of D1 and D2 receptors (Shi et al, 2000). In the present study, we show a decrease in the percentage of spikes in bursts of DA neurons after acute amphetamine (A+1), consistent with previous work (Lodge and Grace, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, a recent report by Twining et al (2015) showed that reductions in nucleus accumbens dopamine transmission induced by an aversive tastant was reversed by administration of a CRF antagonist into the VTA. Similarly, ICV administration of a CRF 1 antagonist increases dopamine neuron population activity and mesoaccumbens dopamine release, 'suggestive of a tonic inhibitory role for CRF on the activity of VTA dopamine neurons' (Lodge and Grace, 2005). Collectively, these previous findings suggest that CRF in the VTA can at least in some instances act in a stimulus-specific manner to attenuate dopamine release, putatively by reducing glutamate and/or enhancing GABA release onto dopamine neurons in the VTA.…”
Section: Crf Actions In the Vta And Effort-related Decision-makingmentioning
confidence: 72%
“…Although we hypothesize that augmented CRF-induced reinstatement was due to alterations in CRF-R2 activity, it is also possible that alterations in CRF-R1 receptors contributed to the effect. CRF-R1 antagonists have been reported to reduce cocaine SA (Goeders and Guerin 2000), cocaineinduced increases in NAcc DA (Lodge and Grace 2005), cocaine-induced conditioned place preference (Lu et al 2003) and stressor-but not cocaine-induced reinstatement Lee et al 2003).…”
Section: Discussionmentioning
confidence: 99%